Assertive Speech Acts in The Twilight Saga Novel - Anggrainy, Dhea Puspita; Masykuroh, Qanita (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to investigate the types and functions of assertive speech acts in The Twilight Saga novel. Methodology: The data of this qualitative text analysis were the speeches of the main female character, Bella, which contains an act of assertive speech. The data were collected using document analysis and were analyzer using the framework of Searle's speech acts theory (1969). Results: The findings show all types of assertive speech acts used by Bella, namely, stating, claiming, describing, reporting and concluding. Furthermore, stating is the most dominant category, reflecting the emotional transparency and honesty which are typical of the romance-fantasy genre. Correspondingly, while concluding is the least due to the storyline's emphasis on feelings rather than logical conclusions. In addition, the functions of assertive speech acts are binding the speaker to the truth of the proposition in stating, claiming, describing, reporting and concluding. Applications/Originality/Value: These results imply that the act of emphatic speech in romantic fiction plays a central role in shaping character intimacy, emotional development, and thematic depth. Future research could expand data across sagas, compare novel-film adaptations, or include multimodal analysis to explore how assertive actis shift across media and narrative contexts.